Can the Use of Internet Applications Increase the Participation of Men in Healthy Lifestyle Behavior? - Maxwell, Karen Denise; Gerrior, Shirley (Archives of Business Research, 2017)
Mortality rates in the United States are higher for men than women as a result of chronic diseases such as heart disease, cancer, and diabetes. Although men suffer from chronic diseases at higher rates than women, few health interventions are targeted to men. Limited knowledge exists regarding the specific components needed to design Internet applications to appeal to men. The purpose of this quantitative study was to examine the relationship between Internet applications and the influence on participation of men in healthy lifestyle behaviors. A quasi-experimental design was used to analyze data collected from the Health Information National Trends Survey (HINTS) (N = 990). A group of men (n = 323) that used Internet applications was compared to a control group of men (n = 667) that did not use Internet applications. The study results are generalizable to men in the United States because of the use of data from HINTS. Results from the regression analysis indicated that Internet applications for self-management of health behavior had a significant effect upon participation in healthy lifestyle behavior t(49) = -2.212, p < .05. There was no significant effect upon men not using Internet applications t(49) = 1.023, p > .05. This study supports the United States federal government’s Healthy People 2020 objective to increase the proportion of people who use Internet applications for health management.